1990
DOI: 10.1128/iai.58.1.179-188.1990
|View full text |Cite
|
Sign up to set email alerts
|

Composition, serologic reactivity, and immunolocalization of a 120-kilodalton tube precipitin antigen of Coccidioides immitis

Abstract: Diagnosis of coccidioidomycosis largely depends on serologic tests. In this investigation, the enzyme-linked immunosorbent assay (ELISA) was used to detect patient immunoglobulin M (IgM) precipitin antibody binding to a 120-kilodalton (kDa) fraction previously isolated from an alkali-soluble, water-soluble extract of the arthroconidial wall and mycelial culture filtrate plus toluene lysate of Coccidioides immitis. Results of the serologic response to this tube precipitin antigen (TP-Ag) in the ELISA correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…The tube precipitin antigen, which frequently reacts with antibodies from patients with coccidioidomycosis, is also detectable on the spherule surface. It has been suggested for that antigen as well that its presentation to host cells may involve the sloughing component of the spherule envelope (9,41).…”
Section: Discussionmentioning
confidence: 99%
“…The tube precipitin antigen, which frequently reacts with antibodies from patients with coccidioidomycosis, is also detectable on the spherule surface. It has been suggested for that antigen as well that its presentation to host cells may involve the sloughing component of the spherule envelope (9,41).…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that two electrophoretically distinct TP antigens can be initially separated from the F+L fraction of C. immitis by ConA chromatography (17). These two fractions were purified and identified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) as 120-and 110-kDa glycoproteins (6,17). Resnick and coworkers (27) have reported that a 21-kDa serine proteinase isolated from the culture filtrate of the parasitic phase of C. immitis also demonstrates reactivity with precipitin antibody from sera of patients with coccidioidomycosis.…”
mentioning
confidence: 99%
“…The immunolocalization of the TP antigen has been evaluated in a previous study by Cole et al (4) using human anti-TP antibodies. The antibodies were isolated from patients' sera by immunoadsorption on 3-O-methylmannose, a carbohydrate which has been shown to react with anti-TP antibodies (4,5). In immunoelectron microscopic analyses of presegmented spherules, the investigators reported that the TP antigen was present within the inner cell wall, being detected at the highest concentration along the plasmalemma (4).…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of the CF antibody response, as measured by serial dilutions of the patient's serum or other biofluid, provides an index of disease involvement. Low titers generally reflect localized disease involving the lungs or a single extrapulmonary site, whereas high titers are consistent with extensive multifocal disease.Previous investigations have established that the TP antigen is a high-molecular-weight, heat-stable polysaccharide or polysaccharide-protein complex (4,5,8,9,15,25) which can be extracted from cell walls by enzymatic treatment (7) or by incubating the walls in 1 N NaOH (10). The CF antigen has been characterized as a heat-labile protein or glycoprotein (8,12,23,24), and although its cellular localization has not been established, evidence suggests that it is of cytoplasmic origin (7,17,23,24).…”
mentioning
confidence: 99%